CSR and Performance of Family Businesses: A Systematic Review - Pintian Lv; Yongqiang Li; Debi Mitra (Australasian Accounting, Business and Finance Journal, 2020)
There have been numerous studies on the relationship between CSR and performance of family businesses. However, academia have yet to come to a consensus regarding the sign and size of the relationship. Neither was there any consistent evidence on the boundary conditions for the relationship between CSR and performance in family businesses. Based on a review of Agency Theory, Stakeholder Theory, Stewardship Theory, Utilitarian Theory and Social Emotional Wealth Theory, this paper addresses the aforementioned research gap based on a systematic review. The study synthesised the literature on performance which is measured in three aspects by the existing literature, namely financial performance, social performance, and innovation. Moreover, the study assessed the empirical literature on the relationship between CSR and the aforementioned three performance measures. The study contributes to the literature by establishing the conceptual foundation for future empirical research.
Keywords: CSR; family business; empirical research